ANALYSIS OF JUDGES' CONDITIONS IN MAKING DECISION ON THE PERSONNEL OF THE CRIME OF MOTORCYCLE THEFT BY UNDERAGE CHILD - Titin Prihatiningsih; Zainab Ompu Jainah (Law Faculty of Universitas Bandar Lampung, 2023)
Every child should ideally grow and develop properly according to their age, but in reality there are children who commit the crime of motorbike theft, namely in Decision Number: 4/Pid Sus-Anak/2022/PN.Tjk. Internal factors that cause underage Childs to commit motorcycle theft crimes are the child's desire to gain material benefits (money) and the low level of education of children who are still junior high school students. The external factor was the solicitation and persuasion of other actors, namely Fajar Riyadi, who asked his children to steal motorbikes. The basis for the judge's consideration in imposing a prison sentence of 4 (four) months in the Women's Correctional Institution for a child is legally proven to fulfill the elements of Article 363 paragraph (1) 4 of the Criminal Code. The judge considered that imprisonment as an effort to improve the child's behavior. Diversion synchronization of crimes committed by underage Childs is that diversion cannot be applied because the maximum penalty for crimes committed by children is 7 (seven) years and the victimdoes not want the diversion process.